Are scientific literacy and students’ environmental attitudes on ecosystem materials and environmental change correlated? - Putri Rahma Dianti; Sueb Sueb (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
This study aims to analyze the relationship between scientific literacy and students' environmental attitudes. Data were collected using a survey method with scientific literacy test instruments and environmental attitude questionnaires. The research samples are 123 students of MAN 1 Kuantan Singingi, Riau. Data were analyzed using Spearman's Correlational test. The results of research for student scientific literacy in three indicators get an average score 65.5 for indicators explaining scientific phenomena, 60 for indicators of scientific design and evaluation and 83.6 for indicators of data interpretation and scientific facts. The results of students' environmental attitudes on the four indicators get an average of 3.9 and 3.7. The results of the correlation test shown that the correlation coefficient of scientific literacy and environmental attitudes is 0.850 > 0.05, which is not correlated. Based on this research, it can be explained that 1) the overall scientific literacy of students is in the moderate category 2) the overall environmental attitude of students is in the high category and 3) There is no correlation between students' scientific literacy and environmental attitudes. Pros and cons were found between the results of this study and previous studies. Further, broader research is needed to explore the causes of these differences, and to state their impact on education in the future.Abstrak Penelitian ini bertujuan untuk menganalisis hubungan antara literasi sains dan sikap lingkungan siswa. Pengumpulan data menggunakan metode survei dengan instrumen tes literasi sains dan angket sikap lingkungan. Sampel penelitian merupakan 123 siswa MAN 1 Kuantan Singingi, Riau. Data dianalisis menggunakan uji Korelasional Spearman. Hasil penelitian untuk literasi sains siswa pada tiga indikator mendapatkan rerata sebesar 65,5 untuk indikator menjelaskan fenomena saintifik, 60 untuk indikator desain dan evaluasi saintifik dan 83,6 untuk indikator interpretasi data dan fakta saintifik. Hasil sikap lingkungan siswa pada empat indikator mendapatkan rerata sebesar 3,9 dan 3,7.  Hasil uji korelasi menunjukkan koefisien korelasi literasi sains dan sikap lingkungan sebesar 0,850 > 0,05, yaitu tidak berkorelasi. Berdasarkan penelitian tersebut dapat dijelaskan bahwa 1) Literasi sains siswa secara keseluruhan berada pada kategori sedang 2) Sikap lingkungan siswa secara keseluruhan berada pada kategori tinggi dan 3) Hasil uji korelasi menunjukkan tidak ada hubungan antara literasi sains siswa dan sikap lingkungan. Ditemukannya pro dan kontra antara hasil penelitian ini dengan penelitian-penelitian sebelumnya. Diperlukan penelitian lanjutan lebih luas untuk menelisik penyebab perbedaan tersebut, dan menyatakan dampaknya bagi pendidikan di masa depan.